Assessing Antisite Defect and Impurity Concentrations in Bi2Te3 Based Thin Films by High‐Accuracy Chemical Analysis. (26th April 2013) - Peranio, Nicola; Winkler, Markus; Dürrschnabel, Michael; König, Jan; Eibl, Oliver
Abstract In Bi2Te3‐based materials charge‐carrier densities are determined by antisite defects and controlling these defects is a key issue for thermoelectric and topological insulator materials. Bi‐Te thin films with high‐quality thermoelectric properties are deposited using a nano‐alloying approach by molecular beam epitaxy (MBE) and sputtering. The in‐plane transport properties are measured at room temperature as a function of charge‐carrier density. High‐accuracy chemical analysis by wavelength‐dispersive X‐ray spectrometry (WDX) is applied for the first time to these Bi2Te3‐based thin films. The acquisition conditions for WDX spectrometry are established using Monte Carlo simulations for the electron trajectories, which guarantees a high lateral resolution and rules out stray radiation generated in the substrate of the films. In contrast to energy‐dispersive X‐ray spectrometry (EDX), which is usually applied, WDX offers unprecedented accuracy for measuring antisite defect concentrations and thus has a high impact on improving the quality of thin films. The charge‐carrier densities are calculated from the WDX results according to the point‐defect model of Miller and Li and the thermopower and electrical conductivity are calculated for different charge‐carrier densities by solving the linearized Boltzmann transport equation. A good quantitative agreement is found for the dependence of the thermopower on stoichiometry, whereas the electrical conductivity is sensitively affected by contaminants.